Innovative developments in deep brain stimulation devices - Della Torre Attilio; La Torre Domenico; Guzzi Giusy; Volpentesta Giorgio; Lavano Angelo (Interdisciplinary Neurosurgery)
Technological advances in DBS hardware and software represent a significant growth area in functional neurosurgery. These advancements have the potential to significantly enhance treatment outcomes and expand the scope of neurological disorders that can be effectively addressed through DBS interventions. The advent of directional deep brain stimulation (DBS) ushers in a new era in neuromodulation, providing enhanced benefits to individuals with Parkinson’s disease, optimizing clinical outcomes more efficiently, and targeting treatment for stubborn symptoms using data-driven approaches. Implementing a multimodal programming strategy and incorporating cutting-edge current fractionation technology and image-guided tools for lead localization and brain sensing reduces reliance on traditional trial-and-error programming methods. This paves the way for a more predictive application of this therapy. These advancements are poised to propel the development of advanced closed-loop stimulation systems that seamlessly integrate continuous data streams, ultimately leading to improved patient care.